Recognizing and addressing environmental microaggressions, know-your-place aggression, peer mediocrity, and code-switching in STEMM - Neikirk, Kit; Silvers, Sophielle; Kamalumpundi, Vijayvardhan; Marshall, Andrea G.; Scudese, Estevão; McReynolds, Melanie; Hinton, Antentor O. (Frontiers in Education, 2023)
Diversity, equity, and inclusion (DEI) initiatives are critical for fostering growth, innovation, and collaboration in science, technology, engineering, mathematics, and medicine (STEMM). This article focuses on four key topics that have impacted many Black individuals in STEMM: know-your-place aggression, environmental microaggressions, peer mediocrity, and code-switching. We provide a comprehensive background on these issues, discuss current statistics, and provide references that support their existence, as well as offer solutions to recognize and address these problems in the STEMM which can be expanded to all historically underrepresented individuals.